Local industrial production in EAC & Uganda (reflecting on the AfCFTA and the emergence of COVID-19): legal framework - Gloria KEMBABAZI (KAS African Law Study Library, 2021)
This paper analyses the state of local industrial production in Uganda and how the emergence of COVID-19 has impacted it. This analysis bears in mind the regional context of Uganda as Partner State of the East African Community and a member of the African Union. Both of these institutions have mechanisms that impact on trade and relatedly on local industrial production, most notably the newly established African Continental Free Trade Area (AfCFTA). Overall, the paper makes a case for furthering local industrial production drawing on the lessons from the economic and developmental impact that the pandemic has wrought on the country.